2011
DOI: 10.1007/s13337-011-0038-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 3′-Terminal Region of Bean common mosaic virus Strains Infecting Common Bean in India

Abstract: Four strains (NL-1, NL-1n, NL-7 and NL-7n) of Bean common mosaic virus (BCMV) prevalent on common bean (Phaseolus vulgaris) in Himachal Pradesh, a north-western Himalayan state of India were compared at the 3 0 terminal region of the viral genome to elucidate variation and relationship among these strains. 3 0 terminal region comprising of partial nuclear inclusion b (NIb) (171-233 bp), complete coat protein (CP) (860 bp) and 3 0 untranslated region (UTR) (208-244 bp) shared 96-98% nucleotide and 96-99% amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Sequencing of BCMV strains DeMV, NL-1, NL-1n, NL-4, NL-7, and NL-7n, as well as some BCMV strains collected in Australia showed that the BCMV CP possess the DAG motif (Coutts et al, 2011;Hamid et al, 2013;Hu et al, 1995;Sharma et al, 2011). Hamid et al (2013) also identified a BCMV-specific conserved motif in the CP amino acid sequence (MVWCIDN) in strains NL-1, NL-4, and NL-7.…”
Section: Molecular Determinants Of Aphid-mediated Transmission and Homentioning
confidence: 99%
See 1 more Smart Citation
“…Sequencing of BCMV strains DeMV, NL-1, NL-1n, NL-4, NL-7, and NL-7n, as well as some BCMV strains collected in Australia showed that the BCMV CP possess the DAG motif (Coutts et al, 2011;Hamid et al, 2013;Hu et al, 1995;Sharma et al, 2011). Hamid et al (2013) also identified a BCMV-specific conserved motif in the CP amino acid sequence (MVWCIDN) in strains NL-1, NL-4, and NL-7.…”
Section: Molecular Determinants Of Aphid-mediated Transmission and Homentioning
confidence: 99%
“…Currently, there are 22 complete BCMV genome sequences and 9 complete BCMNV genome sequences available through NCBI. Sequence data for CP genes and 3 0 -untranslated regions have been used extensively to place BCMV isolates taxonomically (Fang et al, 1995;Sharma et al, 2011). As a result, most partial or complete sequences of BCMV or BCMNV are for the CP gene.…”
Section: Taxonomymentioning
confidence: 99%
“…Another source of emerging genetic variation are recombinations, which benefit viruses in overcoming host resistance and successful infection [10,11]. Many new strains or pathotypes do not behave like traditional BCMV strains and cannot be distinguished, even using the partial sequence of the CP and 3'-UTR of the virus genome [12,13]. Therefore, molecular characterization using whole-genome sequence analysis is currently used as a precise and reliable criterion for the differentiation of BCMV isolates and strains [14].…”
Section: Introductionmentioning
confidence: 99%
“…By 2015, there were 22 BCMV full length genome sequences and 9 BCMNV full length genome sequences available through NCBI currently [13]. 3 0 -UTR sequence data and CP genes have been used to group BCMV isolates [14]. BCMNV is transmitted by seeds up to 83% in Phaseolus vulgaris L and by several aphid species [15].…”
Section: Introductionmentioning
confidence: 99%